2013
DOI: 10.1287/moor.1120.0572
|View full text |Cite
|
Sign up to set email alerts
|

A Fluid Limit for an Overloaded X Model via a Stochastic Averaging Principle

Abstract: We prove a many-server heavy-traffic fluid limit for an overloaded Markovian queueing system having two customer classes and two service pools, known in the call-center literature as the X model. The system uses the fixed-queue-ratio-withthresholds (FQR-T) control, which we proposed in a recent paper as a way for one service system to help another in face of an unexpected overload. Under FQR-T, customers are served by their own service pool until a threshold is exceeded. Then, one-way sharing is activated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 48 publications
0
45
0
Order By: Relevance
“…If class 2 is overloaded, then an optimal ratio r 2,1 should hold between the queues. In [24] we showed that the FQR-T control achieves the target ratios asymptotically as the scale increases (in the fluid limit), for the time-dependent transient performance as well as in steady state. Moreover, the FQR-T control produces a tractable fluid limit.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…If class 2 is overloaded, then an optimal ratio r 2,1 should hold between the queues. In [24] we showed that the FQR-T control achieves the target ratios asymptotically as the scale increases (in the fluid limit), for the time-dependent transient performance as well as in steady state. Moreover, the FQR-T control produces a tractable fluid limit.…”
Section: Introductionmentioning
confidence: 86%
“…By Lemma 3.1 in [24], π 1,2 (γ) is well defined for all γ ∈ S, but D(γ, ·) is positive recurrent if and only if 0 < π 1,2 (γ) < 1 and γ ∈ S b . By Theorem 6.1 of [23], Both the FWLLN and the FCLT depend critically on distributional and topological characteristics of the FTSP's.…”
Section: The Fast-time-scale Processmentioning
confidence: 97%
See 3 more Smart Citations